Post Hysterectomy morbidity: a suburban teaching hospital experience in Kanchipuram, Tamil Nadu, South India - Lakshmi, P. Vijaya; Sheela, Wills G.; Munusamy, M. Mohanambal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the removal of uterus for benign uterine tumor and uterine descent in perimenopausal women. Post hysterectomy and follow up morbidity in rural women is studied over a period of 1 year. They were reviewed during hospital stay to identify morbidity and risk factors for prolonged hospital stay and formulate modalities to reduce morbidity. Risk factors assessed were fever, wound sepsis, anemia, previous post-operative adhesions and injury to other organs. Follow up was done at 4 weeks. 72% women were morbidity free. 46% women had more than one morbidity. The aim of this study is to analyse immediate and late post hysterectomy morbidity in a rural setup and to identify risk factors for prolonged hospitalization and formulate modalities to reduce morbidity and duration of hospital stay. Method: Perimenopausal women who underwent hysterectomy for benign uterine conditions and uterine descent were studied for post-operative morbidity at SSSMCRI over a period of one year. Post hysterectomy morbidity was clinically assessed from day one of surgery till discharge, for early and late morbidity. Abdominal skin incision smear, vault smear, urine culture and USG pelvis for collection of fluid was done in woman who developed fever. Follow-up morbidity was done at 4 weeks. Hysterectomy done for malignant conditions were excluded from the study. Results: In rural women, postoperative morbidity was assessed in 81 abdominal, 32 vaginal hysterectomy. Post-operative pain was felt by all 113 women for first 3 days. Fall of hemoglobin due to haemorrhage was seen in 43 (38%) women. 33 needed post-operative blood transfusion. Surgical site infection was seen in 13, needed re-suturing in 7. Fever was seen in 50 women (44%) due to UTI (E coli 13, Klebsiella 5). Pelvic fluid collection was seen in 9 with vault infection. We had one burst abdomen, one re-laparotomy, 3 bladder injuries. Prolonged hospital stay was seen in 41 women. 46% had more than one morbidity. Follow-up at 4 weeks, 72% were morbidity-free. Prolene granuloma 2, Stitch abscess 9, vaginal discharge 14, vault granuloma 3 were observed. Vaginal smear showed 9 Staphylococcus aureus and 5 bacterial vaginosis infection. 12 women had E. coli and 6 Klebsiella infection in urine culture. Conclusion: Pre-operative risk factors for post op morbidity like anemia, urinary and vaginal infection should be properly treated prior to surgery. Awareness of risk factors for morbidity, anticipation of complications due to size, site, nature of tumour and previous surgery adhesions, timely intervention by experienced surgeons and adequate blood transfusion will reduce morbidity and prolonged hospital stay.